THE Copper Catalyst in Sulfur Reduction Process with Visible Light - Ismail; Bustan, Muhammad Djoni; Haryati, Sri (GoAcademica Research & Publishing, 2025)
Sulfur gas such as SOx is one of the harmful residual gases resulting from combustion in vehicle engines due to the high sulfur content in fuel oil, especially diesel. Conventional processes in sulfur reduction still use technology with high process operating conditions and are expensive, thus charging the selling price of low sulfur diesel oil. Light energy is a promising alternative in sulfur reduction process with low production cost. This research will examine the sulfur reduction process with red light assisted by tin catalyst. The results showed that tin catalyst increased the photon energy in red light with sulfur reduction up to 800 ppm in 10 hours. The removal of C-S and O-H groups indicates the formation reaction of DBTO2 after DBT can be cracked from diesel oil hydrocarbon.